Fast linear sum assignment with error-correction and no cost constraints - Bougleux, Sebastien; Gauzere, Benoit; Blumenthal, David B.; Brun, Luc (Pattern Recognition Letters, 2020)
We propose an algorithm that efficiently solves the linear sum assignment problem with error-correction and no cost constraints. This problem is encountered for instance in the approximation of the graph edit distance. The fastest currently available solvers for the linear sum assignment problem require the pairwise costs to respect the triangle inequality. Our algorithm is as fast as these algorithms, but manages to drop the cost constraint. The main technical ingredient of our algorithm is a cost-dependent factorization of the node substitutions.
CRIS-Team Scopus Importer:2021-05-26
Keywords: Graph edit distance; Inexact graph matching; Linear assignment